VD_FINDINFO HC / 2013 / 51 vom 24. Januar 2013 - VD Tribunal cantonal (2013)
CHOSE JUGÉE, CONDITION DE RECEVABILITÉ, DÉCISION D'IRRECEVABILITÉ | 42 CC, 132 al. 3 CPC (CH), 59 al. 2 let. e CPC (CH), 60 CPC (CH)